Factors associated with dental caries in children aged 4-6 years old - Widayati, Nur (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTDental caries is one of the dental health problems. Dental caries are formed because there was leftover food that sticks to the teeth, which eventually lead to tooth calcification. Impact, teeth become brittle, hollow, even broken.Dental caries experience a loss of power to make a child chewing and digestive disruption, which resulted in growth of less than the maximum. This study aims to determine the relationship of parentsâ behavior towards the maintenance of dental health of children (feeding habits sweet, sticky and drinking milk, teeth maintenance, inspection tooth and mouth) with dental caries in the TK R.A Bustanussholihin in Balun village Turi District of Lamongan. This study Analytics whose data is collected with a cross sectional sample of kindergarten children aged 4â6 years with a total sample of 49 children. The collection of primary data through interviews parents TK R.A Bustanussholihin student using questionnaires and secondary data obtained from the agency are in the region of the profile data TK R.A Bustanussholihin in Balun Village of Turi District of Lamongan. This study used a correlation coefficient of contingency. Based on the results of the contingency coefficient correlation test showed that the factors that have a strong relationship is the habit of feeding the sweet, sticky, and drink milk with a value of P = 0.504. While the factors that have a weak link is the habit of maintaining dental hygiene habits of children and child oral examination . From this study it can be concluded that there is a relationship or a strong correlation between feeding habits sweet, sticky and drinking milk with the incidence of dental caries in children aged 4â6. So as to prevent dental caries severity we need to hold counseling on feeding sweet, soft and gooey on the effect of dental caries as well as how it should be formula feeding or breast milk to the child to prevent rampant caries.Keywords: dental caries, sweetened food, children aged 4â6 years